Identification of a melanosomal membrane protein encoded by the pink-eyed dilution (type II oculocutaneous albinism) gene. - Rosemblat, S (1994)
The pink-eyed dilution (p) locus in the mouse is critical to melanogenesis; mutations in the homologous locus in humans, P, are a cause of type II oculocutaneous albinism. Although a cDNA encoded by the p gene has recently been identified, nothing is known about the protein product of this gene. To characterize the protein encoded by the p gene, we performed immunoblot analysis of extracts of melanocytes cultured from wild-type mice with an antiserum from rabbits immunized with a peptide corresponding to amino acids 285-298 of the predicted protein product of the murine p gene. This antiserum recognized a 110-kDa protein. The protein was absent from extracts of melanocytes cultured from mice with two mutations (pcp and p) in which transcripts of the p gene are absent or greatly reduced. Introduction of the cDNA for the p gene into pcp melanocytes by electroporation resulted in expression of the 3.3-kb mRNA and the 110-kDa protein. Upon subcellular fractionation of cultured melanocytes, the 110-kDa protein was found to be present in melanosomes but absent from the vesicular fraction; phase separation performed with the nonionic detergent Triton X-114 confirmed the predicted hydrophobic nature of the protein. These results demonstrate that the p gene encodes a 110-kDa integral melanosomal membrane protein and establish a framework by which mutations at this locus, which diminish pigmentation, can be analyzed at the cellular and biochemical levels.